Comparative Study Between Conventional Didactic Lectures and MCQ-Based Reinforcement in Enhancing Learning and Retention Among Undergraduate Medical Students - Jayant Jain; Harshila Jain; Avinash M J (International Journal of Health Sciences and Research, 2026)
Background: Conventional didactic lectures remain widely used in undergraduate medical education; however, passive learning may limit student engagement and long-term retention. Multiple-choice question (MCQ)-based reinforcement may facilitate active recall, formative assessment, and sustained learning. This study compared conventional didactic lectures with MCQ-integrated teaching for improving learning outcomes and knowledge retention among undergraduate medical students. Methods: A prospective quasi-experimental comparative educational intervention study was conducted among Phase III Part 1 MBBS students at a tertiary care teaching institution in Bengaluru, India. Of 248 eligible students, 216 participated (87.1%) and were allocated into two teaching groups of 108 students each. The control group received conventional didactic lectures, whereas the intervention group received didactic lectures supplemented with 25 validated MCQs addressing factual knowledge, interpretation, and clinical application, followed by immediate feedback and explanations. Learning outcomes were assessed using pre-test, immediate post-test, and four-week retention test scores. Student perceptions of MCQ-based reinforcement were assessed using a structured five-point Likert-scale questionnaire. Between-group comparisons were performed using independent t-tests, with paired t-tests used for within-group comparisons. Results: The baseline characteristics and pre-test scores were comparable between groups. The MCQ reinforcement group demonstrated significantly higher post-test scores than the didactic lecture group (79.2 ± 8.1% vs. 67.3 ± 7.8%; p